Penurunan Logam Berat Kromium (Cr) dalam Air Menggunakan Adsorben Ampas Tebu: Indonesia - Ramadhan, Sahrul; Lestari, Puji; Siswoyo, Eko (Teknik Lingkungan Universitas Islam Indonesia, 2026)
Chromium (Cr) is a heavy metal that is toxic, persistent, and potentially carcinogenic. Cr is widely produced from industrial activities such as leather tanning, textiles, and metal plating, making its presence in liquid waste a serious concern. This study aims to investigate the efficiency of reducing Cr concentrations in water using a sugarcane bagasse-based adsorption method, as well as to determine the effect of adding humic acid on enhancing adsorption effectiveness. The study was conducted in batch mode at the Water Quality Laboratory of the Environmental Engineering Program at the University of Islam Indonesia. The parameters varied included pH, contact time, and initial Cr concentration, while the adsorbent characterization was performed using FTIR and SEM. In this study, sugarcane bagasse was used as an adsorbent that had been carbonized at 350°C and sieved to a 50-mesh size. Cr concentration was anlyzed using SSA. Characterization result showed the presence of hydroxyl (-OH), carbonyl (C=O), and aromatic groups in sugarcane bagasse, as well as a porous surface morphology that supports the adsorption process. Optimal conditions were achieved at pH 3, contact time 1440 minutes, and Cr concentration 5 mg/L. The addition of humic acid was found to increase adsorption efficiency by 22,5%. The apporpriate ishoterm model is Langmuir with a maximum adsorption capacity of 1,52 mg/g, while the adsorption kinetics follow the pseudo second order model with rate constant K of 0,0496 g/mg·min.